Dental prevention and disease awareness in children with congenital heart disease - Koerdt, Steffen; Hartz, Julia; Hollatz, Stefan; Frohwitter, Gesche; Kesting, Marco Rainer; Ewert, Peter; Oberhoffer, Renate; Deppe, Herbert (Clinical Oral Investigations, 2018)
OBJECTIVES: The importance of excellent oral health is known to be crucial in children with congenital heart diseases (CHD). Data about dental health and disease awareness is limited. This study aims to assess preventive measures taken to improve dental health in children with CHD and to gain insight into disease awareness and knowledge about the importance of oral health in children with CHD and to propose measures that could be taken. MATERIAL AND METHODS: Parents of 150 children with CHD were asked to complete a questionnaire containing specific questions about the preventive measures taken by the parents and dental and medical practitioners and their knowledge about underlying disease and the importance of oral health. RESULTS: Our results show an absence of information in parents concerning preventive measures and oral hygiene. Knowledge of the indications for antibiotic prophylaxis and for actually given medications was lacking. Preventive dental measures were not performed according to current guidelines. CONCLUSIONS: Knowledge of parents about the importance of oral health in children with CHD could be improved. However, specialized centers involving pediatric cardiologists and pediatric dentists could coordinate the education of parents at an early stage. Moreover, general dentists should be trained more frequently concerning the indications for antibiotic prophylaxis, in particular, and the dental care of children with chronic diseases, in general. Warning cards such as the heart pass should be issued to parents of children with CHD. CLINICAL RELEVANCE: The current study reveals the need for the structured training of medical and dental practitioners to support parents of children with CHD.
EVALuna2:33957